Annealing Kinetics of the Interstitial Carbon–Dioxygen Complex in Silicon. Issue 14 (15th May 2019) - Ayedh, Hussein M.; Grigorev, Aleksei A.; Galeckas, Augustinas; Svensson, Bengt G.; Monakhov, Edouard V.
Abstract : The interstitial carbon‐interstitial dioxygen complex (Ci O2i ) has a deep state close to the mid bandgap of Si and can be an efficient recombination center. In this work, the annealing kinetics of Ci O2i in p‐type, boron doped, Czochralski grown (Cz) silicon are studied. Two sets of samples are irradiated at room temperature (RT) with 1.8 MeV protons to doses of 1 × 10 13  cm −2 (set A) and 5 × 10 13  cm −2 (set B). After irradiation, the samples of both sets are pre‐annealed at 400 °C for 30 h in order to anneal out the well‐known interstitial carbon‐interstitial oxygen (Ci Oi ) complex and to form the Ci O2i complex. The annealing of Ci Oi and formation of Ci O2i is monitored by deep level transient spectroscopy (DLTS) via observation of the corresponding electronic levels at 0.36 eV and 0.39 eV above the valence band edge ( EV ), respectively. The samples are then subjected to isothermal annealing treatments in the temperature range 450–550 °C. The annealing of Ci O2i follows a first order kinetics, exhibiting an activation energy of 2.55 eV, and a pre‐exponential factor in the range (2–30) × 10 12  s −1 . The kinetics and the deduced parameters suggest that Ci O2i anneals out by dissociation rather than diffusion mechanism. Abstract : Ci O2i complex has a deep level near the silicon mid bandgap and might act as a recombination center, limiting the minority carrier lifetime. This paper reports annealing studies of Ci O2i in p‐type Cz‐Si that follow first‐order kinetics, exhibiting an activation energy of 2.55 eV and a pre‐factor within the range (2–30)×10 12  s −1 . The deduced parameters suggest annealing by dissociation mechanism.